Weighted general cumulative entropy and a goodness of fit for normality. Issue 20 (8th September 2021) - Park, Sangun
Abstract: We propose a weighted general cumulative entropy by employing the comparison distribution function, and provide the asymptotic distribution of its estimator. We also discuss the characterization property, and suggest a goodness of fit test based on the general cumulative entropy for normality.